Detection of ICAM-1 in experimentally induced colitis of ICAM-1-deficient and wild-type mice: an immunohistochemical study - Bendjelloul, F; Rossmann, P; Malý, P; Mandys, V; Jirkovská, M; Prokesová, L; Tucková, L; Tlaskalová-Hogenová, H (The Histochemical journal, 2000)
Adhesion molecules (e.g. ICAM-1, CD 54) are known to be upregulated on activated vascular endothelial cells during inflammatory reactions. To study the role of ICAM-1 in intestinal inflammation in vivo, we induced acute experimental colitis in wild-type (C57BL/6) mice and ICAM-1-deficient mice, by feeding the animals with 3% dextran sodium sulphate (DSS) in drinking water for 7 days. In the control strain the immunohistochemical staining showed a very pronounced endothelial upregulation of ICAM-1 after the DSS treatment observed in areas of inflammatory infiltrate, especially in venules or arterioles of the propria and submucosa, and partly in the mesocolon. DSS-fed ICAM-1-deficient mice showed no endothelial enhancement and only faint staining of venules or capillaries approaching that encountered in the control ICAM-1-deficient animals. Our data indicate that ICAM-1 may play a crucial role in the development of acute intestinal inflammation, consistent with our finding that ICAM-1 deficiency can obviate severe forms of experimentally induced colitis in mice.
Keywords: mutantní kmeny myší; kolon; Inflammation; Up-Regulation; cévní endotel; Colitis; upregulace; imunohistochemie; mezibuněčná adhezivní molekula-1; Endothelium, Vascular; Intercellular Adhesion Molecule-1; zánět; Mice, Mutant Strains; Animals; Dextran Sulfate; ženské pohlaví; Immunohistochemistry; zvířata; Colon; myši inbrední C57BL; myši; Mice, Inbred C57BL; kolitida; Mice; Female; síran dextranu